2008
DOI: 10.21273/jashs.133.6.794
|View full text |Cite
|
Sign up to set email alerts
|

Verification of Mandarin and Pummelo Somatic Hybrids by Expressed Sequence Tag–Simple Sequence Repeat Marker Analysis

Abstract: Somatic hybridization is a powerful tool for the genetic improvement of citrus rootstocks, and it is part of an efficient in vitro-based breeding system described here. An essential component of the system is the requirement of confirming tetraploidy and the combination of the two donor genomes. Expressed sequence tag–simple sequence repeat (EST-SSR) markers provide a means to accomplish both of these objectives, and their application to a population of pummelo [Citrus grandis Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…After a significant quantity of callus is obtained, callus lines can be habituated by subculturing on growth regulator free EME or H?H medium (Table 1). At this point, each callus line should be checked by analysis of robust genetic markers, such as SSRs, to assure nucellar rather than zygotic origin; we have occasionally found that embryogenic callus can originate from zygotic embryos in undeveloped aborted ovules (Chen et al 2008). It generally takes a year to have adequate quantities of embryogenic callus for suspension initiation.…”
Section: Embryogenic Callus/suspension Induction and Maintenancementioning
confidence: 99%
See 2 more Smart Citations
“…After a significant quantity of callus is obtained, callus lines can be habituated by subculturing on growth regulator free EME or H?H medium (Table 1). At this point, each callus line should be checked by analysis of robust genetic markers, such as SSRs, to assure nucellar rather than zygotic origin; we have occasionally found that embryogenic callus can originate from zygotic embryos in undeveloped aborted ovules (Chen et al 2008). It generally takes a year to have adequate quantities of embryogenic callus for suspension initiation.…”
Section: Embryogenic Callus/suspension Induction and Maintenancementioning
confidence: 99%
“…Recovered tetraploids should undergo molecular analysis to determine if they are autotetraploids or allotetraploid somatic hybrids, with both having potential value to subsequent conventional breeding schemes. Previously, somatic hybrids have been validated by isozymes, RAPD or CAPS (Grosser and Gmitter 2005); more recently unambiguous and reliable EST-SSR markers with fragments separated on a sequencer, has been the method of choice (Chen et al 2008). EST-SSRs have a further advantage of ploidy level validation in many instances, as up to four different alleles may be identified at a single locus in a somatic hybrid plant.…”
Section: Somatic Hybrid Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to other molecular markers, SSR (simple sequence repeat) markers are now more widely used in genetic, systematic, and comparative genomic studies largely due to their co-dominance, multi-alleles among closely related genomes, and relatively inexpensive development and detection procedures (Chen et al, 2006). These polymorphic, co-dominant, and segregating alleles greatly facilitate authentication and tracking of genetically-related cultivars and hybrids (Chen et al, 2008). 'Orah' mandarin was reportedly bred by Pinhas Spiegel-Roy and Aliza Vardi at The Volcani Center, Israel, with 'Temple' tangor (♀) (Citrus reticulata × C. sinensis) and 'Dancy' mandarin (♂) (C. reticulata) reported as the parents (Jaffa, undated;Saunt, 2000;Greenberg et al, 2004;Tietel et al, 2009;Citrogold, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Identification of the pollen parent of an outcross can be difficult if there are multiple possible pollen sources nearby with similar traits. Under this circumstance, codominant simple sequence repeat (SSR) markers, along with other types of DNA markers, are useful for distinguishing parentage (Chen et al, 2008a(Chen et al, , 2008bDirlewanger et al, 2004). This approach is more effective and informative if the SSR markers contain polymorphic heterozygous alleles that will help distinguish among the possible pollen parents (Chen et al, 2008a).…”
mentioning
confidence: 99%